The patrons and their poor: Jewish community and public charity in early modern Germany - Ḳaplan, Devorah (Jewish culture and contexts, 2020)
"Patterns of giving tell us about both donors and recipients-not only about their finances but about their values, perceptions, roles in society, and the dynamics of power that existed between and among those who gave and those who received. The Patrons and Their Poor uses the lens of public charity to provide an intimate portrait of the early modern Ashkenazic community. The prism of charity allows for this expanded view of daily life in the Jewish community"--